1987
DOI: 10.1111/j.1365-2133.1987.tb05795.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis-like lesions during long-term penicillamine therapy for Wilson's disease

Abstract: Systemic sclerosis-like lesions developed in a 14-year-old boy with Wilson's disease who had been treated with D-penicillamine for 11 years. Clinical and laboratory manifestations included proximal scleroderma, pulmonary restrictive defects, positive antinuclear antibodies, and the deposition of C3 at the dermal-epidermal junction of the lesional skin. This is the first case reported in which long-term administration of penicillamine was followed by the development of systemic sclerosis-like lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This fact may be due to the suppressive effect of OPC (6,7). Although these keloidal lesions developed during OPC therapy and OPC is known to cause various cutaneous manifestations (8,9,(13)(14)(15), it is unlikely that the keloidal lesions were caused by OPC. Bernstein et al (8) described a patient with seronegative erosive arthritis of the rheumatoid type who developed morphea-like skin lesions after 14 months of treatment with OPC (250 mg/day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact may be due to the suppressive effect of OPC (6,7). Although these keloidal lesions developed during OPC therapy and OPC is known to cause various cutaneous manifestations (8,9,(13)(14)(15), it is unlikely that the keloidal lesions were caused by OPC. Bernstein et al (8) described a patient with seronegative erosive arthritis of the rheumatoid type who developed morphea-like skin lesions after 14 months of treatment with OPC (250 mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of systemic sclerosis (SS) with nodular scleroderma have been only rarely reported (1)(2)(3)(4)(5). Although several studies have suggested that D-penicillamine (DPC) may be effective in the treatment of SS (6) and localized scleroderama (7), morphea-like reactions (8) and SSlike lesions (9) during DPC therapy have also been described. We report here a case of SS which developed nodular scleroderma during DPC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We found levels of phospholipase A2 significantly greater than those in aqueous humour from patients with senile cataracts. 2 It is interesting to note that phosphatidylcholine is readily degraded by aqueous humour phospholipase A2. On the other hand, lysophosphatidylcholine is known to harm the lens in experimental models of cataract development; so another possible role for phospholipase A2 in tissue damage should be added to the list.…”
mentioning
confidence: 99%